Physicochemical Characterization and Aquaculture Suitability of Taudaha Lake, Kathmandu, Nepal - Poudel , Samichhya; Parajuli, Indira (Journal of Nepal Hydrogeological Association, 2025)
Taudaha Lake, the only natural lake in Kathmandu, Nepal, was studied to evaluate its potential for aquaculture following the Nepal Water Quality Guidelines for Aquaculture (NWQGA, 2015). The study aimed to characterize physicochemical parameters, determine hydrochemical processes, and assess suitability for fish farming. Ten water samples were collected during January 2024 from strategically selected sites around Taudaha Lake, including inflow and outflow points as well as accessible locations along the lake boundary. In-situ measurements included temperature, pH, dissolved oxygen (DO), electrical conductivity (EC), and total dissolved solids (TDS). Laboratory analyses measured total hardness, alkalinity, major cations (Ca²+, Mg²+, Na+, K+), anions (Cl-, SO4 ²-, HCO3-), and nutrients (ammonia, phosphate) following APHA-AWWA-WEF (2017) standard methods. Results indicated that most parameters, including temperature (15.9–17.2 °C), pH (7.45–7.92), TDS (211–223 mg/L), phosphate (0.018 0.188 mg/L), and ammonia (0.030–0.097 mg/L), were within NWQGA limits, supporting cold and intermediate water fish species. However, DO levels (2.76–5.54 mg/L) were below recommended thresholds, and total hardness (98–150 mg/L) exceeded optimal limits potentially limiting fish growth and reproduction. Geochemical analyses using Piper, Gibbs, and mixing diagrams revealed a mixed Ca²+–Mg²+–Cl-–SO4 ²- hydrochemical facies dominated by silicate and carbonate weathering with minimal anthropogenic influence. Overall, Taudaha Lake shows moderate aquaculture suitability. Long-term water quality monitoring, management of nutrient inputs, and maintenance of adequate oxygen levels are recommended to improve fish productivity while preserving the lake’s ecological and cultural values.